2009
DOI: 10.1042/bst0371167
|View full text |Cite
|
Sign up to set email alerts
|

VEGF resistance as a molecular basis to explain the angiogenesis paradox in diabetes mellitus

Abstract: The action of VEGF (vascular endothelial growth factor) is essential to maintain proper endothelial and vascular function. VEGF stimulates virtually all aspects of endothelial function, namely proliferation, migration, permeability and nitric oxide production and release. In addition, the action of VEGF makes the endothelium anti-apoptotic. In turn, the inhibition of VEGF action is associated with endothelial dysfunction. Likewise, endothelial dysfunction can be found in the presence of several cardiovascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
76
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 22 publications
(24 reference statements)
4
76
0
3
Order By: Relevance
“…The attenuated VEGF signal transduction, VEGF resistance, has been postulated as the molecular mechanism underlying the dysregulation of angiogenesis in people with type 2 diabetes [3,11]. Our observation that SeP impairs angiogenic processes is noteworthy in the context of experimental data suggesting that SeP plays a role in the anti-oxidative defense system [13].…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…The attenuated VEGF signal transduction, VEGF resistance, has been postulated as the molecular mechanism underlying the dysregulation of angiogenesis in people with type 2 diabetes [3,11]. Our observation that SeP impairs angiogenic processes is noteworthy in the context of experimental data suggesting that SeP plays a role in the anti-oxidative defense system [13].…”
Section: Discussionmentioning
confidence: 51%
“…Therefore, VEGF resistance, a defect of VEGF-related signal transduction, has been postulated as a molecular basis for the dysregulated angiogenesis in diabetes mellitus [3,11]. The molecular mechanisms underlying VEGF resistance in diabetes mellitus are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Increased expression of VEGF-A as well as FGF1 and transcription factor E2F8, which we observed in adipose tissue of obese individuals with IGT as comparted to obese men with NGT, can contribute to enhancement of angiogenesis, but development of insulin resistance is also associated with vascular endothelial growth factor resistance despite the presence of functionally active VEGF receptor 1 [36]. It is important to note that the expression of FGFR2, which predominantly interacts with both FGF1 and FGF2 and responsible for enhanced angiogenesis, is up-regulated in adipose tissue of obese individuals with NGT, but slightly down-regulated in obese patients with IGT and this down-regulation is associated with additional increase of FGF1 gene expression.…”
Section: Discussionmentioning
confidence: 87%
“…It is suggested that without considering the serum VEGF level, the VEGF signaling pathway is impaired during diabetes which is considered as VEGF resistance 28,29 . Therefore, it is possible that reduced serum NO concentration may be responsible for lower neovascularization in hindlimb ischemic tissue of diabetic animals.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, serum NO concentration in diabetic animals was lower than control. Enhanced angiogenesis has an important role in some complications of diabetes including diabetic retinopathy and nephropathy, on the other hand, reduced angiogenesis which is related to lower arteriogenesis and poor growth of collateral artery has an important role in cardiovascular diseases in diabetes 2,19 . NO not only enhances angiogenesis, but also, other angiogenic growth factors exert their angiogenic response through increasing NO production 20 .…”
Section: Discussionmentioning
confidence: 99%